Proteins, Small Peptides and Other Signaling Molecules Identified as Inconspicuous but Possibly Important Players in Microspores Reprogramming Toward Embryogenesis - Dubas, Ewa; Żur, Iwona; Moravčiková, Jana; Fodor, József; Krzewska, Monika; Surówka, Ewa; Nowicka, Anna; Gerši, Zuzana (Frontiers in Sustainable Food Systems, 2021)
In this review, we describe and integrate the latest knowledge on the signaling role of proteins and peptides in the stress-induced microspore embryogenesis (ME) in some crop plants with agricultural importance (i.e., oilseed rape, tobacco, barley, wheat, rice, triticale, rye). Based on the results received from the most advanced omix analyses, we have selected some inconspicuous but possibly important players in microspores reprogramming toward embryogenic development. We provide an overview of the roles and downstream effect of stress-related proteins (e.g., β-1,3-glucanases, chitinases) and small signaling peptides, especially cysteine—(e.g., glutathione, γ-thionins, rapid alkalinization factor, lipid transfer, phytosulfokine) and glycine-rich peptides and other proteins (e.g., fasciclin-like arabinogalactan protein) on acclimation ability of microspores and the cell wall reconstruction in a context of ME induction and haploids/doubled haploids (DHs) production. Application of these molecules, stimulating the induction and proper development of embryo-like structures and green plant regeneration, brings significant improvement of the effectiveness of DHs procedures and could result in its wider incorporation on a commercial scale. Recent advances in the design and construction of synthetic peptides–mainly cysteine-rich peptides and their derivatives–have accelerated the development of new DNA-free genome-editing techniques. These new systems are evolving incredibly fast and soon will find application in many areas of plant science and breeding.